Prospects of graphene and carbon nanotube for nanoscale interconnects - Rayhan, Md. Shakhawat Hossain; Uddin, Md. Shifat; Biva, Jannatul Tazrin; Huda, Md. Shofiqul (BRAC University, 2018)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2017.